RMB internationalisation and currency co-operation in East Asia - Ulrich Volz (Universität Leipzig, Wirtschaftswissenschaftliche Fakultät, 2013)
This paper scrutinises the state of RMB internationalisation and its likely progress over the coming years and discusses its implications for currency co-operation in East Asia. As part of its internationalisation, the RMB is gradually delinked from the dollar, which will effectively put an end to the East Asian dollar standard that has shaped the region's financial architecture over the last three decades and that has provided a relatively high degree of intra-regional exchange rate stability. Because of the close trade and investment ties that have developed across the region, the East Asian countries, especially the ASEAN countries which are striving to create an ASEAN Economic Community, will continue to manage their exchange rates and stabilise their currencies against one another to facilitate cross-border investment and commerce. But instead of a replacing of the dollar standard with an RMB standard we are likely to see some rather loose and informal exchange rate co-operation in East Asia based on currency baskets, with China herself moving towards a managed exchange rate system guided by a currency basket.
Keywords: E58; F33; 330; RMB internationalisation; key currencies; Chinese economy; East Asian monetary co-operation; currency baskets